2018
DOI: 10.21926/obm.geriatr.1901030
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of How the ‘Household Model' of Care Can Contribute to Positive Ageing for Residents in the ‘Fourth Age’

Abstract: Background: Promoting a good quality of life for the oldest members of society has become a top priority as evidenced in UK policy. The 'household' model is a departure from traditional approaches to care provision since it offers person-centred support-combing health and social care-to older people in specially-designed, small, homelike environments. Having gained increasing popularity in care homes across developed countries, the impact of this model of service delivery on residents' quality of life and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…Maintaining at least a modicum of social involvement and independence may evidence of ageing successfully, whereas the requirement of care (at home or in an institution) is not. The move from one to another need not be stark and could be a gradation of care, moving from full independence, through family support and supported living environments, such as shared living environments (single building or complexes) as championed by Atul Gwande [54] and Julia Neuberger [55] in their books and more latterly "Dementia Villages" providing a secure environment for people with dementia and their families [56]. Even when dependency increases such that more intensive support is needed a more positive outlook may be experienced by those in institutionalized care than those living at home [57].…”
Section: Positive Ageingmentioning
confidence: 99%
“…Maintaining at least a modicum of social involvement and independence may evidence of ageing successfully, whereas the requirement of care (at home or in an institution) is not. The move from one to another need not be stark and could be a gradation of care, moving from full independence, through family support and supported living environments, such as shared living environments (single building or complexes) as championed by Atul Gwande [54] and Julia Neuberger [55] in their books and more latterly "Dementia Villages" providing a secure environment for people with dementia and their families [56]. Even when dependency increases such that more intensive support is needed a more positive outlook may be experienced by those in institutionalized care than those living at home [57].…”
Section: Positive Ageingmentioning
confidence: 99%
“…At the other end of the spectrum are small household designs that support “person-centered” models of care ( Ahmed et al, 2019 ; Kaup, 2015 ; Rabig et al, 2006 ). The architecture and interior features are scaled down and designed to focus primarily on replicating a residential environment with the goal of resident autonomy and quality of life ( Abushousheh et al, 2011 ; Proffitt et al, 2010 ; see Figure 2 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The architecture and interior features are scaled down and designed to focus primarily on replicating a residential environment with the goal of resident autonomy and quality of life ( Abushousheh et al, 2011 ; Proffitt et al, 2010 ; see Figure 2 ). Households (HHs) are defined as a small group of residents who live together in a clearly defined setting that has a front door and contains a functional kitchen, a dining room, and a living room ( Ahmed et al, 2019 ; Carnemolla et al, 2021 ; Shields & Norton, 2006 ). The composition of these living areas (LAs) can vary but one of the first distinctions as a HH (beyond the small size of 10–12) is the proximity of resident bedrooms to the social spaces ( Kaup, 2003 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, LTC policies in Canada have prioritised biomedically-oriented quality of care [ 2 ], but over time, a culture change towards a more person-centred model of care has evolved [ 3 ]. Additional research [ 4 7 ], among others, has indicated that a home-like approach to care creates more opportunities for residents’ overall quality of life (QoL) and wellbeing [ 8 , 9 ]. Accordingly, many LTC oriented policies now reflect a broad spectrum of person-centered QoL indicators, for instance, early research describing 11 domains, such as meaningful activity, relationships, dignity, autonomy, and privacy [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%